Dynamics of migration to and from Nariño. Exploration of recent and absolute migrations, intercensal period 1993-2005 - Villamarín Martínez, Francisco Javier; Ortega Ordoñez, Ximena Alexandra (Sociedad y Economía, 2018)
The purpose of this paper is to analyze the dynamics of internal migration in Nariño, Colombia, in the intercensal period 1993-2005. The method used is the secondary analysis of demographic statistics, such as those presented by the matrices of lifelong migration and recent migration that has produced the Latin American and Caribbean Demographic Center (Celade) of the Economic Commission for Latin America and the Caribbean (ECLAC), through the MIALC database (Internal Migration in Latin America and the Caribbean). The results show that in Nariño immigrations and emigrations, both lifelong and recent ones, have as origin and as destination nearby provinces such as Valle del Cauca, Cauca and Putumayo; they also show that an important part of these movements is explained by the migrations to and from Bogotá. In addition, it was confirmed that lifelong migrations are more voluminous and cumulative than recent migrations, as several investigations have already announced.